Determinants of Market Share of Islamic Commercial Banks in Indonesia in the Economic System - Shafira, Alfina; Rizal, Sofyan; Aziz, Roikhan Mochamad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
This research analyzes the impact of the BI Rate, CAR, ROA, FDR, as well as Murabahah and Musyarakah financing, on the market share of Islamic Commercial Banks (BUS) in Indonesia. Using quantitative panel data regression on quarterly data from 7 BUSs covering the period 2015-2024, the study found that all tested variables significantly affect market share. The BI Rate, as a macroeconomic factor, showed significance, indicating the sensitivity of Islamic banking to external economic conditions and monetary policy. Internal factors such as CAR (Capital Adequacy Ratio) and ROA (Return on Assets) positively and significantly influenced market share, aligning with Islamic economic principles of maintaining stability and wealth. FDR (Financing-to-Deposit Ratio) also had a positive effect, highlighting the link to real sector financing. On the product side, Murabahah, the dominant financing contract, proved individually significant. Musyarakah, although less utilized due to higher risk, also exerted a positive influence, underscoring the potential of Profit-Loss Sharing (PLS) schemes in Islamic finance. Overall, the findings indicate that BUS market share is influenced by a combination of external factors (BI Rate), internal health (CAR, ROA), and a focus on real sector financing (FDR, Murabahah, Musyarakah), implying a connection between the fundamental performance of Islamic banks and the real sector they finance.